The Effect of Simple Melodic Lines on Aesthetic Experience: Brain Response to Structural Manipulations. (29th December 2014) - Ferri, Stefania; Meini, Cristina; Guiot, Giorgio; Tagliafico, Daniela; Gilli, Gabriella; Di Dio, Cinzia
Abstract : This fMRI study investigates the effect of melody on aesthetic experience in listeners naïve to formal musical knowledge. Using simple melodic lines, whose syntactic structure was manipulated, we created systematic acoustic dissonance. Two stimulus categories were created: canonical (syntactically "correct, " in the Western culture) and modified (made of an altered version of the canonical melodies). The stimuli were presented under two tasks: listening and aesthetic judgment. Data were analyzed as a function of stimulus structure (canonical and modified) and stimulus aesthetics, as appraised by each participant during scanning. The critical contrast modified versus canonical stimuli produced enhanced activation of deep temporal regions, including the parahippocampus, suggesting that melody manipulation induced feelings of unpleasantness in the listeners. This was supported by our behavioral data indicating decreased aesthetic preference for the modified melodies. Medial temporal activation could also have been evoked by stimulus structural novelty determining increased memory load for the modified stimuli. The analysis of melodies judged as beautiful revealed that aesthetic judgment of simple melodies relied on a fine-structural analysis of the stimuli subserved by a left frontal activation and, possibly, on meaning attribution at the charge of right superior temporal sulcus for increasingly pleasurable stimuli.